Effects of a single dose of oral estrogen on left ventricular diastolic function in hypertensive postmenopausal women with diastolic dysfunction - FAK, ALİ SERDAR (My University, 2000)
OBJECTIVE: To evaluate the acute effects of a single dose of oral estrogen on left ventricular diastolic function in hypertensive postmenopausal women with diastolic dysfunction. DESIGN: Prospective, double-blind, placebo-controlled, clinical study. SETTING: Cardiology and postmenopausal outpatient clinics of a university hospital. PATIENT(S): Thirty postmenopausal women with hypertension (diastolic blood pressure of >90 mm Hg) and left ventricular diastolic dysfunction (mitral E/A ratio [the ratio of peak velocity of early mitral diastolic filling to late diastolic filling] of <1 and isovolumic relaxation time of >100 ms) were included in the study. Thirty normotensive postmenopausal women with normal left ventricular diastolic function served as the control group. INTERVENTION(S): Conjugated equine estrogen (0.625 mg) was given orally. Left ventricular diastolic function was assessed by Doppler echocardiography at baseline and 3 hours after the administration of estrogen. MAIN OUTCOME MEASURE(S): Left ventricular diastolic filling as assessed by Doppler echocardiography. RESULT(S): Estrogen had no effect on heart rate or blood pressure in either study group. The baseline E/A ratios were 0.72 +/- 0.26 and 1.22 +/- 0.30, and the isovolumic relaxation times were 122 +/- 18 ms and 89 +/-14 ms in the hypertensive and normotensive groups, respectively. Estrogen had no significant effect on any of the Doppler parameters in the normotensive group. In the hypertensive group, there was a trend toward normalization of the E/A ratio (from 0.73 +/- 0.11 to 0.84 +/- 20) and a significant improvement in the isovolumic relaxation time (from 124 +/- 20 ms to 105 +/- 13 ms) in response to the administration of estrogen compared with placebo. CONCLUSION(S): A single dose of oral estrogen caused a significant improvement in left ventricular diastolic filling in hypertensive postmenopausal women with diastolic dysfunction.
Keywords: Female; Humans; Middle Aged; Blood Pressure; Hypertension; Postmenopause; Double-Blind Method; Prospective Studies; Heart Rate; Placebos; Diastole; Echocardiography, Doppler; Estrogens, Conjugated (USP); Ventricular Dysfunction, Left